Integration of Binary Active Sites: Co3V2O8 as Polysulfide Traps and Catalysts for Lithium‐Sulfur Battery with Superior Cycling Stability. Issue 18 (13th April 2020) - Zhang, Linlin; Wan, Fang; Cao, Hongmei; Liu, Lili; Wang, Yijing; Niu, Zhiqiang
Abstract: Lithium‐sulfur (Li‐S) batteries as a promising energy storage candidate have attracted attention due to their high energy density (2600 Wh kg −1 ). However, the serious shuttle effect caused by the dissolution of the lithium polysulfides (LiPS) in electrolyte significantly degrades their cycling life and rate performance. Herein, the "binary active sites" concept in a Li‐S battery system via the design of a cobalt vanadium oxide (CVO) modified multifunctional separator is designed. In the case of CVO, active vanadium sites simultaneously anchor the LiPS through the chemical affinity and active cobalt sites can dominate a rapid kinetic conversion. Such a synergistic effect contributes to improving the utilization of sulfur in the electrochemical process for the enhanced electrochemical performance. As a result, the Li‐S battery with the CVO modified separator possesses a high reversible capacity of 1585.5 mAh g −1 at 0.1 C and superior cycling stability with 0.012% capacity decay cycle −1 after 3000 cycles. More impressively, the assembled soft‐packaged Li‐S devices can exhibit the excellent stability under bending states. This binary active sites strategy provides a route to design the functional materials for modifying separators of Li‐S batteries to improve the performance. Abstract : Cobalt vanadium oxide (CVO) with the integration of binary Co and V sites is utilized to modify the separator of a lithium‐sulfur battery for achieving superior cycling performance. The synergistic effect of chemical interaction and catalytic activity in CVO can not only immobilize lithium polysulfides via the chemical interaction, but also accelerate their conversion for enhancing electrochemical performance.